Sonocatalytic Oxidation of Reactive Blue 29 by N-doped TiO2 from Aqueous Solution - Hossein Kamani; Simin Nasseri; Ramin Nabizadeh; Mehdi Khoobi; Davoud Ashrafi; Edris Bazrafshan; Amir Hossein Mahvi (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Sonocatalytic process as an advanced oxidation process is considered for degradation of pollutants in aqueous solution. The aim of this study was to increase the removal of dye by doping of TiO2 with non-metal element such as nitrogen. Materials and methods: Un-doped and N-doped TiO2 nano-particles with different nitrogen contents were synthesized by a simple sol–gel method in laboratory. X-ray diffraction (XRD), Field emission scanning electron microscopy (FE-SEM), Energy dispersive X-ray analysis (EDX), and UV–visible diffuse reflectance spectra (UV-vis DRS) were used for characterization of the synthesized nanoparticles. The sonocatalytic activity of synthesized nanoparticles was evaluated by investigating degradation of reactive blue 29 under ultrasonic radiation and the effects of nitrogen doping content, different initial pH of solution, and dye concentration. Results: The study showed that both un-doped and doped nano-particles were in nano-sized that tend to agglomerate. By using different nano-particles, the highest sonocatalytic activity was achieved by 0.6 N-doped TiO2 with 58 % after 90 min of ultrasonic irradiation. Effect of initial pH of aqueous solution showed that the sonocatalytic activity decreased by increase in initial pH. Conclusion: Sonocatalysis using N-doped TiO2 was found to be an effective method for degradation of textile dyes. The high sonocatalytic activity could be attributed to the band gap narrowing and anatase phase in TiO2 nanoparticles. Sonocatalytic degradation followed the Langmuir–Hinshelwood kinetic model (R2 = 0.98) with a rate constant of 0.01 mg L−1 min−1.